Dissecting the allosteric FXR modulation: a chemical biology approach using guggulsterone as a chemical tool. Issue 8 (3rd July 2019) - Passeri, Daniela; Carotti, Andrea; Pittol, Jose M. Ramos; Ciaccioli, Gianmario; Pellicciari, Roberto; van Mil, Saskia W. C.; Gioiello, Antimo
Abstract : FXR allosteric pockets might act as potential targets for small molecules to selectively interfere with the metabolic action of the receptor. Abstract : Guggulsterone is a promiscuous ligand for endocrine and metabolic lipid receptors traditionally used to treat a number of diseases including diabesity, hyperlipidemia, atherosclerosis, and osteoarthritis. Although relatively weak, its activity at the farnesoid X receptor (FXR) is particularly intriguing as guggulsterone acts as an antagonist with a peculiar ability of gene selective modulation. We report here a chemical biology study with the aim to further characterize the biological action of guggulsterone at the FXR and to obtain further insights into the functional role played by noncanonical FXR binding pockets S2 and S3. Our results suggest that the FXR accessory pockets might act as potential targets for small molecules able to modulate the metabolic activation of the receptor without affecting the anti-inflammatory activity thus revealing a new approach for disclosing selective FXR modulators that might bypass potential side-effects from chronic treatments.